Comitês de Resolução de Disputas (Dispute Boards) nos contratos da administração pública: análise de eficiência, potencialidades e melhores práticas - Domingues, Igor Gimenes Alvarenga (2022)
The present dissertation seeks to analyze the efficiency, potential and best practices in the use of Dispute Boards in Public Administration contracts. Therefore, the work is based on international experience to point out the origin, basic characteristics, and modeling of the use of the mechanism, which is recommended by the main international organizations and associations that are dedicated to its study. Next, an analysis of a vast database with several infrastructure projects that adopted the Dispute Board is carried out, in order to ascertain the concrete results proven by its use. In the second part, the study focusses at the national reality, pointing out the reasons that justify the use of the Dispute Board by the Public Administration, in addition to the estimated costs and types of contract in which its use makes sense. It also assesses the history of its implementation in national contracts, the supporting legislation that currently exists and on-going bills in the National Congress. Closing this part, the study evaluates some real cases in which courts and control agencies analyzed the mechanism. The third part of the work addresses the structuring of Dispute Board clauses in public contracts, with propositional recommendations. Finally, some points with a high potential for dissent are highlighted, suggesting actions to minimize risks. The dissertation follows a hybrid research model based on problem solving and best practices.